The Logic of Condom Use in Female Sex Workers in Bali, Indonesia - Pande Putu Januraga (International Journal of Environmental Research and Public Health, 2020)
Studies on human immunodeficiency virus (HIV) prevention practices of female sex workers often examine the use of condom as a single behaviour: using or not using condom. This study explores typologies of the logic of condom use as part of exercising meaningful identities from female sex workers’ perspectives. We employed in-depth interviews with a purposely selected 35 female sex workers in Bali, Indonesia. Information from the in-depth interviews was analysed using thematic framework analysis to develop typologies of female sex workers’ experiences on the logic of condom use and its relation to the construction of identity. We identified two main logics for not using condom: the prioritising of financial stability and romantic relationships over condom use. The main logic for using condom was to protect their health in order to improve their future economic security. Embedded within these logics, women chose to practise agency and negotiate meaningful identities consistent with their ideals of being responsible mothers, successful migrant workers and loyal partners. Our study concluded that female sex workers had clear logics for both the use and non-use of condom with their clients, highlighting the rational nature of female sex workers decision making.